CONCEPTUAL APPROACHES TO IMPROVING THE QUALITY OF THE EDUCATIONAL SYSTEM IN UZBEKISTAN - Buriboevich, Rakhmatov Bahriddin; Buriboev (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: In the article, taking into account the fact that it is becoming urgent to improve the quality of training of highly educated specialists in New Uzbekistan, a special state program was adopted in this regard. Method: Within the framework of the state program, conceptual approaches and directions to the problems of improving the quality of education are analyzed. Results: Conclusions and suggestions on improving the quality of education are recommended. Novelty: Taking into account the fact that it is becoming urgent to improve the quality of training of highly educated specialists in New Uzbekistan, a special state program was adopted in this regard.